Prosdocimo de' Beldomandi: Contrapunctus - Prosdocimo de' Beldomandi; Herlinger, Jan W. (Lincoln and London University of Nebraska Press, 1984)
In the Contrapunctus (1412) Prosdocimo surveys the practice of counterpoint and musica ficta, codifying each in six rules. Unlike most of his contemporaries, who were satisfied merely to state their rules, Prosdocimo justified his, making the treatise a primer of the musical aesthetics of his time.
Keywords: Composing